Effective improvement depth for ground treated with rapid impact compaction - Mohammed Mohammed, M.; Hashim, Roslan; Firas Salman, A. (2010)
Ground improvement has been used on many construction sites to densify granular material, in other word, to improve soil properties and reduce potential settlement. This paper evaluates the efficiency of rapid impact compaction (RIC), which is an improvement on the process of deep dynamic compaction, in ground improvement. In this technique, ground improvement is achieved by impacting the ground with a 7 tone weight, 35 times/min, and drop height of 0.8 m at 2.5 m C/C square grid spacing. Method evaluation is made by comparing the tip resistance of pre-treatment and post treatment cone penetrometer test (CPT) soundings. However, the effective improvement depths and the factors affecting the depth are discussed, and a formula for calculating the effective depth is presented. Vibration monitoring was conducted to check the effect of the vibrations born by RIC machine on the adjacent structures to assess how much the process is considered environmentally friendly and accordingly the challenging locations it can reach especially in the urban areas. It was found that the RIC succeeded in achieving the required degree of improvement, improvement depth depends on soil properties and energy applied; and the effective improvement depth formula presented by this study is true when the soil is granular and homogeneous with depth. Vibrations by RIC machine were within allowable limits and with controlled effect on the adjacent structures.